Pentagalloyl Glucose- A nd Ethyl Gallate-Rich Extract from Maprang Seeds Induce Apoptosis in MCF-7 Breast Cancer Cells through Mitochondria-Mediated Pathway - Jiraporn Kantapan (2020)
© 2020 Jiraporn Kantapan et al. Bouea macrophylla Griffith, locally known as maprang, has important economic value as a Thai fruit tree. The maprang seed extract (MPSE) has been shown to exhibit antibacterial and anticancer activities. However, the bioactive constituents in MPSE and the molecular mechanisms underlying these anticancer activities remain poorly understood. This study aims to identify the active compounds in MPSE and to investigate the mechanisms involved in MPSE-induced apoptosis in MCF-7 treated cancer cells. The cytotoxic effect was determined by MTT assay. The apoptosis induction of MPSE was evaluated in terms of ROS production, mitochondrial membrane potential depolarization, and apoptosis-related gene expression. The compounds identified by HPLC and LC/MS analysis were pentagalloyl glucose, ethyl gallate, and gallic acid. MPSE treatment decreased cell proliferation in MCF-7 cells, and MPSE was postulated to induce G2/M phase cell cycle arrest. MPSE was found to promote intracellular ROS production in MCF-7 treated cells and to also influence the depolarization of mitochondrial membrane potential. In addition, MPSE treatment can lead to increase in the Bax/Bcl-2 gene expression ratio, suggesting that MPSE-induced apoptosis is mitochondria-dependent pathway. Our results suggest that natural products obtained from maprang seeds have the potential to target the apoptosis pathway in breast cancer treatments.